Between-task competition for intentions and actions. Issue 8 (August 2013) - Millington, Rebecca S.; Poljac, Edita; Yeung, Nick
People can switch quickly and flexibly from one task to another, but suffer the effects of between-task competition when they do so: After switching, they tend to be distracted by irrelevant stimulus information and hampered by incorrect actions associated with recently performed tasks. This competition results in performance costs of switching, as well as a bias against switching when there is choice over which task to perform, particularly when switching from a difficult task to an easier one. Two experiments investigated the locus of these between-task competition effects in voluntary task switching. Participants switched between an easy location classification and a harder shape classification, making two responses on each trial: the first to register their task choice, the second to perform the chosen task on a subsequently presented stimulus. The results indicated that participants chose to perform the difficult shape task more often than the easier location task, evidence that between-task competition affects intentions that are expressed independently of task-specific actions. The bias was stronger in participants with faster choice speed, suggesting that these influences are relatively automatic. Moreover, even though participants had unlimited time to choose and prepare a task before stimulus presentation, their subsequent performance was nonetheless sensitive to persisting effects of between-task competition. Altogether these results indicate the pervasive influence of between-task competition, which affects both the expression of global task intentions and the production of task-specific actions.